Penerapan Pembelajaran Berdiferensiasi pada Tema Perkembangan Teknologi untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Chairul Azmi (Jurnal Didaktika Pendidikan Dasar, 2024)
This research was motivated by the low learning outcomes of students on the theme of technological development in Class III. The research was conducted with the aim of discussing and obtaining information about the Application of Differentiated Learning on the Theme of Technology Development to Improve Learning Outcomes of Elementary School Students The type of research conducted was Classroom Action Research (PTK). The location of this research is at SD Negeri 19 Kuamang. The subjects in this study were grade III students of SD Negeri 19 Kuamang with a total of 30 people. This research was carried out in the even semester of the 2022/2023 academic year (January-June) starting in February 2023. The research process is divided into two cycles, each with four stages: preparation, execution, observation, and reflection. Techniques for collecting data include observation, experiments, documentation, and field notes. Data analysis is carried out using percentage calculations. The results showed that the use of differentiated learning models can improve student learning. This is shown by the increasing percentage of student learning outcomes pre-cycle, cycle I, and cycle II which are respectively 23%, 53%, and 90%. Therefore, it can be concluded that the use of differentiated learning can improve the learning outcomes of SD Negeri 19 Kuamang students in grade III.